2006
DOI: 10.1158/0008-5472.can-05-3312
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Exposure to Lead Chromate Causes Centrosome Abnormalities and Aneuploidy in Human Lung Cells

Abstract: Hexavalent chromium [Cr(VI)] compounds are established human lung carcinogens. The carcinogenicity of Cr(VI) is related to its solubility, with the most potent carcinogens being the insoluble particulate Cr(VI) compounds. However, it remains unknown why particulate Cr(VI) is more carcinogenic than soluble Cr(VI). One possible explanation is that particulates may provide more chronic exposures to chromate over time. We found that aneuploid cells increased in a concentration-and time-dependent manner after chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 33 publications
5
47
0
1
Order By: Relevance
“…Cr(VI) is a well-established human lung carcinogen and previous studies show that Cr(VI) chromium is most potent in particulate form. Particulate Cr(VI) induces DNA strand breaks, Cr-DNA adducts, Cr-DNA crosslinks and mutation to 6-thioguanine resistance in diploid human fibroblasts [8,[14][15][16][17]12,35,36], however how these lesions are repaired and their relationship to Cr(VI)-induced CIN are uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…Cr(VI) is a well-established human lung carcinogen and previous studies show that Cr(VI) chromium is most potent in particulate form. Particulate Cr(VI) induces DNA strand breaks, Cr-DNA adducts, Cr-DNA crosslinks and mutation to 6-thioguanine resistance in diploid human fibroblasts [8,[14][15][16][17]12,35,36], however how these lesions are repaired and their relationship to Cr(VI)-induced CIN are uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the two centrosomes form the poles of the bipolar mitotic spindle. Holmes et al (2006) showed that chronic exposure to lead chromate causes centrosome abnormalities and aneuploidy using WTHBF-6 cells, a cell line derived from normal human bronchial fibroblasts. Hexavalent chromium compounds [Cr(VI)] are human lung carcinogens (Le´onard & Lauwerys, 1980), and "particulate" Cr(VI) compounds are one of the most potent forms.…”
Section: Centrosome Abnormalities In Human Lung Cancer: Mechanisms Camentioning
confidence: 99%
“…One or more of these species induces DNA double strand breaks, which are sensed directly by gamma-H2A.X and the MRN complex, which binds DNA, unwinds the ends and recruits ATM, ultimately leading to repair (5-7). Failure to repair these breaks leads to neoplastic transformation, possibly through the generation of chromosome instability, which has also been observed after particulate Cr(VI) exposure (32,33). …”
Section: Discussionmentioning
confidence: 99%